2015
DOI: 10.3390/rs70506454
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Precipitation Datasets in South America and West Africa based on Satellite-Derived Rainfall, Enhanced Vegetation Index and Digital Elevation Model

Abstract: Mean Annual Precipitation is one of the most important variables used in water resource management. However, quantifying Mean Annual Precipitation at high spatial resolution, needed for advanced hydrological analysis, is challenging in developing countries which often present a sparse gauge network and a highly variable climate. In this work, we present a methodology to quantify Mean Annual Precipitation at 1 km spatial resolution using different precipitation products from satellite estimates and gauge observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Brunsdont et al [31] put forward a local regression model called Geographically Weighted Regression (GWR) to handle the problem of spatial nonstationary. GWR-based satellite precipitation downscaling algorithm was found to perform better than the two global-regression-based algorithms over various regions on TRMM product, at both annual scale and monthly scale [15,30,32].…”
Section: Advances In Meteorologymentioning
confidence: 94%
“…Brunsdont et al [31] put forward a local regression model called Geographically Weighted Regression (GWR) to handle the problem of spatial nonstationary. GWR-based satellite precipitation downscaling algorithm was found to perform better than the two global-regression-based algorithms over various regions on TRMM product, at both annual scale and monthly scale [15,30,32].…”
Section: Advances In Meteorologymentioning
confidence: 94%
“…Even though the continuous development of CHIRPS is mainly in support of drought-related issues in Africa (Climate Hazards Group, 2016), there are now other global applications available (e.g. http://ewx.chg.ucsb.edu:8080/EWX/index.html, http:// chg.geog.ucsb.edu/tools/geowrsi/index.html) and also papers that have looked at climate dynamics in South America (Ceccherini et al, 2015;Deblauwe et al, 2016).…”
Section: Chirpsv2mentioning
confidence: 99%
“…The CCD-derived estimates are then merged with World Meteorological Organization's Global Telecommunication System (GTS) gauged data using a 'smart interpolation' approach . Comparisons with other satellite precipitation estimates and observed rainguage data have shown that this data set provides useful long-term precipitation estimates for Africa (Ceccherini et al, 2015;Dembélé and Zwart, 2016;Toté et al, 2015). In addition, this dataset has been used in the East Africa region 15 previously to provide high resolution and combined gauge-satellite precipitation estimates (Ayana et al, 2016;Pricope et al, 2013).…”
Section: Climate Datamentioning
confidence: 92%